Performance Evaluation of The Apparatus at The Intersection of Jl. Teuku Umar-Jl. Pemuda and Jl. Sawunggaling - Jl. Basuki Rahmat Bojonegoro District - Soegyarto; Yulis Widhiastuti; Andy Yanuar Putra Riyadi (Journal of Green Science and Technology, 2025)
Along with the increasing progress and development in society, the desire to use time and money is very necessary. Population growth in an urban area is always followed by an increase in space requirements. In Bojonegoro itself, which is one of the cities of industry, tourism, and education that cannot be separated from the movement of traffic in and out of both people and goods. So there are many intersections that connect roads to shopping centers, offices, government, housing, and roads to the city center. One of the intersections in Bojonegoro is the intersection of Jl. Teuku Umar-Jl. Pemuda and Jl. Sawunggaling-Jl. Basuki Rahmat Bojonegoro Regency which has a fairly high transportation density during working time hours, so the use of traffic signals is needed. This causes the traffic flow that passes through to continue to experience changes in vehicle volume, especially at certain hours which causes delays in travel due to increased traffic flow. In order to avoid travel delays due to increased traffic flow, improvements in traffic management are needed. This study aims to analyze and evaluate the performance of the intersection of Jl. Teuku Umar-Jl. Pemuda and Jl. Sawunggaling-Jl. Basuki Rahmat Bojonegoro Regency using the PKJI 2023 method. From the results of the analysis, it is found that there is a need for an additional phase from 2 phases to 4 phases so that there is no queue length and the number of vehicles stopped on the East Approach (Jl. Pemuda) is too long and many. Keyword: intersections, traffic, transportation, traffic signals.